How Does Instability Affect Bench Press Performance? Acute Effect Analysis with Different Loads in Trained and Untrained Populations - Moisés Marquina; Jorge Lorenzo-Calvo; Carlos García-Sánchez; Alfonso de la Rubia; Jesús Rivilla-García; Amelia Ferro-Sánchez (MDPI AG, 2023)
(I) The execution of different sports involves a significant number of throws, jumps, or direction changes, so the body must be as stable as possible while performing a specific action. However, there is no classification of unstable devices and their influence on performance variables. Furthermore, the effect on athletes' experience using instability is unknown. (II) The aim of this study was to analyze the power and speed parameters in bench press with different loads and unstable executions: (1) stable (SB), (2) with asymmetric load (AB), (3) with unstable load (UB), (4) on fitball (FB) and (5) on a Bosu® (BB). A total of 30 male participants (15 trained and 15 untrained) were evaluated for mean propulsive speed (MPS), maximum speed (MS), and power (PW) with different types of external load: a low load (40% of 1RM), medium load (60% of 1RM), and high load (80% of 1RM) in each condition. Variables were measured with an inertial dynamometer. (III) The best data were evidenced with SB, followed by AB (3-12%), UB (4-11%), FB (7-19%), and BB (14-23%). There were no differences between groups and loads (p > 0.05) except in the case of MS with 60% 1RM, where trained participants obtained 4% better data (p < 0.05). (IV) Executions with implements and equipment such as fitball and Bosu® do not seem to be the most recommended when the objective is to improve power or execution speed. However, situations where the load is unstable (AB and UB) seem to be a good alternative to improve stabilization work without high performance. Furthermore, experience does not seem to be a determining factor.